Utility of Point-of-Care COVID-19 Testing in an Outpatient Otolaryngology clinic. Issue 4 (October 2021) - Ganesh, Meera; Brawley, Craig Cameron; Khanwalkar, Ashoke; Mycanka, John; Conley, David B.; Kern, Robert C.; Tan, Bruce K.
Objective: To evaluate the utility of point-of-care COVID-19 testing for identifying infected patients in an otolaryngology practice. Study Design: Retrospective review of 947 patients tested with a point-of-care nucleic acid amplification test for SARS-CoV-2 (Abbott ID Now). Setting: Tertiary otolaryngology clinic setting from July to November 2020. Methods: Tests were characterized by provider-specified indication (symptomatic, preprocedural, and universal), subspecialty, provider type, and contemporaneous regional COVID-19 positivity rate, defined as 12%. Positive results were further classified as true or false positive (TP or FP) based on repeat polymerase chain reaction testing wherever available, and true positivity rates were compared among groups by multiway chi-square and Fisher's exact tests. FP rates within 48 hours of a TP result were also evaluated to assess for batch contamination. Results: A total of 947 SARS-CoV-2 nucleic acid amplification tests were performed, yielding 9 TPs (0.95%) and 5 FPs (0.53%). TP rates were significantly different by testing indication, with higher rates among symptomatic patients ( P = .012; vs universal, odds ratio = 7.86 [95% CI, 1.27-83.52]; vs preprocedural, odds ratio = 4.91 [95% CI, 0.79-52.17]); by subspecialty ( P = .011), as driven by higher positivity rates in laryngology; and by encounter, with higher rates among advanced practice practitioners than physicians ( P = .002; odds ratio = 9.97 [95% CI, 2.11-51.16]). TP rates were not significantly different during periods of uncontrolled local outbreak ( P = .660). FP rates were not significantly higher within a 48-hour window of a TP ( P = .192). Conclusion: Point-of-care COVID-19 nucleic acid amplification tests in an outpatient otolaryngology clinic identified a low TP rate (<1%) with most cases being clinically suspected. Laryngology and advanced practice practitioner encounters may have higher positivity rates. Level of evidence: 3.